High-power GaSb-based microstripe broad-area lasers. (22nd February 2018) - Lu, Zefeng; Wang, Lijie; Zhang, Yu; Shu, Shili; Tian, Sicong; Tong, Cunzhu; Hou, Guanyu; Chai, Xiaoli; Xu, Yingqiang; Ni, Haiqiao; Niu, Zhichuan; Wang, Lijun
Abstract: A simple and effective approach based on the microstripe broad-area (MSBA) structure was proposed, and high-efficiency and high-power mid-infrared GaSb-based quantum well lasers were demonstrated. It was shown that the MSBA structure can effectively suppress the lateral current leakage and improve the temperature behavior of GaSb lasers. Compared with the conventional broad-area structure, the energy conversion efficiency of MSBA lasers was more than threefold and threshold current density decreased above 50%. High characteristic temperature and high beam quality were realized.